Droga jako synonim zbawienia w Koranie. Refleksje lingwistyczno-teologiczne - Marek Micherdziński (Polonia Sacra)
The metaphor of the way is one mode of seeing the salvation. Quran as the Holy Book of salvation for the Muslim believers attempts to handle the religious experience in category of the way. The metaphor of the way is in Quran expressed by the words of Arabic voculary derivated from the triliteral verbal root { ﺪﻫى } hdy. They are firstly the nominal derivatives: ﻫُﺪًى hudan – „right guidance, right way, right path, true religion” (S. II, 2. 38). Quran as the Book of Salvation to a people who believe is named: ﻫُﺪًى ﻭرَحْﻤَﺔ hudan wa-raḥmatan – „a guidance and a mercy” (S. VII, 52; XVI, 64.89; XXVII, 76–77; XXXI, 2– ﻫُﺪًى ﺑﻭشُْﺮَى ,( 3 hudan wa-bušrà – „guidance and glad tidings” (S. II, 97; XXVII, 1–2) oraz ﻫُﺪًًى ﻭشِ ﺎﻔء hudan wa-šifāʼun – „a guide and a cure” (S. XLI, 44). In Torah, Gospel Book and Quran „was guidance and light” for those who have Taqwà of Allāh (S. V, فﻴهِ ﻫُﺪًى ﻮﻧﻭرٌ : 46 fīhi hudan wa-nūrun). The synonims of way leadings to salvation are the followings terms: سَ ﻴﺒلُ ﷲِﺍ sabīlu l-Lāhi – „the cause of Allāh” i صِﺮَﺍط ﻤﻟﺍُﺴْ ﻘﺘ ﻢِﻴُ ṣirātu l-mustaqīmu – „correct guidance”. However the noun ﻫﺎَدٍ hādin – „the Guide” is one of theophanic names of Allāh (S. XXII, 54; XXV, 31). The verbal derivatives serve to define of the divine action in believers life (S. II, 143. 198; VI, 87; XVI, 36; XXXIX, 18; XCIII, ﻫَﺪَى : 7 hadà – „guided”). Allāh „guide” ( ﻳَهْﺪِى yahdī) the people who believe to the salvation, to the truth and to Himself. He is absolutely independent in giving salvation, it's signified with phrase ﻣَنْ ﻳشََﺎء man yašāʼu – „whom He wills” (S. II, 142. 213. 272; VI, 88; X, 25; XVI, 4. 93; XXIV, 35. 46; XXVIII, 56; XXXV, 8). The blievers are named أ ﻤﻟُهْ ﺪﺘُ ﻥﻭَ ʼal-muhtadūna – „the guided” (S. Vi, 82). The antithesis of the verb „guide” is verb أضَلﱠ ʼaḏalla – „leads astray” (S. LXXIV, 31). The expressions the mutual experiential base is connected with the Bible whose name is nomadism. The ancient Hebrews and Arabs were nomads. Therfore the metaphoric of way serves to name the various spheres of his life and culture. The metaphore of divine guidance the man to the salvation in Quran has the pattern in the biblical texts. The hebrew equivalents to the expressions are the words of Hebrew vocabulary derivated from the more verbal roots: { נחה } nẖh, { דרך } drk, { אשׁר } ʼšr, { ארח }ʼrẖ, { עגל } ʻgl, { נתב } ntb, { סלה } slh. The biblical texts are for the author of Quran starting-point to moulding the own conception of salvation. The elaborated in this article expressions serve to describe one of the divine action of salvation. It relies on guidance of the believers on the right way to salvation. The name of Allāh, „The Guide”, is guarding the man from the mistakes on this way.